COVID-19 Vaccine Uptake in the Context of the First Delta Outbreak in China During the Early Summer of 2021: The Role of Geographical Distance and Vaccine Talk - Zhang Q; Shi Y; English AS (Dove Medical Press, 2022)
Qionghan Zhang,1 Yanwei Shi,2 Alexander Scott English2 1School of Business Administration, Zhejiang Gongshang University, Hangzhou, People's Republic of China; 2Department of Psychology and Behavioral Sciences, Zhejiang University, Hangzhou, People's Republic of ChinaCorrespondence: Alexander Scott English, Department of Psychology and Behavioral Sciences, Zhejiang University, Xixi Campus, Tianmushan road 44, Hangzhou, 310000, People's Republic of China, Tel +86 15900502194, Email AEnglish@zju.edu.cnPurpose: Vaccination is essential to control the prevalence of COVID-19. However, vaccine hesitancy has been a major issue globally. Some studies have suggested that community outbreaks might boost vaccine uptake. Consistent with that idea, vaccination rates increased dramatically during the first outbreak of the COVID-19 Delta variant in Guangdong, China, in June 2021. Based on the risk perception attitude theory, this study attempted to explore the joint effect of geographical distance to the outbreak and the frequency of talking about the COVID-19 vaccine (vaccine talk) on people's COVID-19 vaccine uptake.Methods: An anonymous self-report online questionnaire was completed by citizens living in Guangdong Province, China, from June 6 to 11, 2021, during the Delta variant outbreak in that region. The relationship between COVID-19 vaccine uptake, geographical distance to the epicenter of the outbreak, and vaccine talk was analyzed using logistic regression analysis.Results: Data from 350 respondents were included in the final analysis. Results showed a negative association between geographical distance and COVID-19 vaccine uptake. Furthermore, the relationship was moderated by vaccine talk. Specifically, when individuals infrequently discussed vaccine talk with others, close distance to the epicenter of the outbreak served as a motivator for getting vaccinated, whereas for people who frequently discussed the vaccine, geographical distance might have played less of a role in motivating them to get vaccinated.Conclusion: This research highlights the joint effect of geographical distance to the outbreak of COVID-19 and vaccine talk in COVID-19 vaccine uptake. While the findings may only be a starting point for launching a public health awareness campaign, encouraging people to engage in more conversations about vaccines may be a promising solution for future health emergencies, especially among people far from the outbreak.Keywords: COVID-19 vaccination, geographical distance, risk perception attitude, health communication